2006
DOI: 10.1149/1.2181428
|View full text |Cite
|
Sign up to set email alerts
|

Models for the Chemical Vapor Deposition of Tin Oxide from Monobutyltintrichloride

Abstract: Global kinetic mechanisms and models are developed to describe the growth of tin oxide ͑SnO 2 ͒ films from monobutyltintrichloride ͑MBTC͒ by chemical vapor deposition. Several candidate mechanisms are examined. Deposition from MBTC + O 2 mixtures is best described by a mechanism in which MBTC reacts with an oxygen-covered surface, while deposition from MBTC + O 2 + H 2 O mixtures can be effectively predicted using a mechanism in which a gas-phase MBTC-H 2 O complex is formed, adsorbed by the surface, and react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Apart from material characteristics, deposition control is vital for industrial processes and requires knowledge of the reaction kinetics [16,17]. It was previously reported that there is a wide spread of deposition rate characteristics presented in the literature [3,[17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from material characteristics, deposition control is vital for industrial processes and requires knowledge of the reaction kinetics [16,17]. It was previously reported that there is a wide spread of deposition rate characteristics presented in the literature [3,[17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The reaction mechanism is based on modeling of deposition rates measured in a low pressure stagnation-flow reactor [7,13], but we have slightly modified the reaction constant in the surface reaction to fit the experimental data (see Table 3). It has been found that the deposition rate predicted by the CFD model with the original mechanism matches well with the experimental measurement far away from the inlet slot but about four times higher underneath the inlet slot (see Fig.…”
Section: Cfd Model For Tin Oxide Depositionmentioning
confidence: 99%
“…The current model is developed using CFD with an impinging flow geometry, and explicitly accounts for homogenous reaction in the gas phase, heterogeneous reaction on the glass surface, thermal effect of the impinging jet on the glass, and impinging flow characteristics in the confined coating zone. The reaction kinetics are based on modeling of deposition rates measured in a stagnation-flow reactor [7,13]; certain kinetic parameters were modified to fit the experimental data. A comparison of CFD model predictions with experimental measurements shows that the experimentally observed spatial distribution in the deposition rate profile is successfully captured by the model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although reactions of tin tetrachloride with water and oxygen are relatively fast, Eley-Rideal mechanisms are not very likely since the loss of entropy and the minimal chance that molecules collide in the exact configuration needed for a reaction will give an extremely low pre-exponential factor, and so reaction rate. 9 The last group is represented by Chae et al 10,11 who interpreted their results also in terms of an Eley-Ridealtype of mechanism during his study on monobutyl tin chloride (MBTC, n-C 4 H 9 SnCl 3 ) with oxygen. However, for the deposition of MBTC with oxygen and water, the authors proposed that first a gas-phase complex of MBTC with water must be formed before the complex can adsorb at the surface and react with oxygen in an Eley-Rideal-type of reaction.…”
Section: Introductionmentioning
confidence: 99%